Molecular mechanisms and therapeutic progress in atherosclerosis: bridging immune inflammation and precision medicine - Han, Yimin; Xu, Hongyi; Yao, Xinlei; Li, Zhanzhan; Zhu, Chuli; Li, Xia; Chen, Bingqian; Sun, Hualin (Frontiers in Immunology, 2026)
Atherosclerosis, a chronic vascular disease characterized by lipid-driven inflammation and arterial wall remodeling, remains the leading cause of cardiovascular morbidity and mortality. This review aims to systematically summarize recent advances in our understanding of its multidimensional pathogenesis and the corresponding evolution of therapeutic strategies. We focus on the intricate crosstalk between endothelial dysfunction, dyslipidemia, and immune-inflammatory activation, which collectively drive disease progression. Key mechanisms discussed include metabolic reprogramming of immune cells, phenotypic switching of vascular smooth muscle cells, and novel modes of programmed cell death. Beyond conventional lipid-lowering approaches, we highlight emerging therapeutic avenues such as immunomodulatory vaccines, RNA-based therapeutics, and biodegradable stents with inherent anti-ferroptotic properties. Furthermore, we explore the potential of modernized traditional Chinese medicine formulations that target multiple pathways. Looking forward, we conclude that integrating multi-omics data, single-cell technologies, and artificial intelligence is pivotal for advancing precision medicine. This integration will enable the development of individualized risk prediction models and targeted interventions, ultimately bridging the gap between molecular mechanisms and effective clinical management to overcome current bottlenecks in atherosclerosis prevention and treatment.